Pengembangan Video Tutorial Berbasis Aplikasi Canva pada Materi Selling and Promotion di SMK Akomodasi Perhotelan - Rezkia Anjani Firstian; Neni Rohaeni; Yoyoh Jubaedah (Akademi Pariwisata NHI Bandung, 2022)
This study aims to develop audio-visual learning media in the form of video tutorials on selling and promotion materials. The video tutorial presents a visualization of the move, which comes from a collection of various objects arranged in a sequence according to a predetermined flow at each time. The method used in this study is descriptive with a PPE approach, namely Planing, Production, Evaluation. Based on the results of validation carried out by material experts and media experts, it is stated that the video tutorials developed are suitable for use as learning media at SMK Hospitality Accommodation.